Experimental and numerical investigation on the strength of polymer-metal hybrid with laser assisted metal surface treatment. Issue 10 (19th May 2019) - Ma, Fangwu; Chen, Shixian; Han, Lu; Wang, Zhuojun; Pu, Yongfeng
Abstract: The aim of this study was to evaluate the effect of laser assisted treating metal surface on the strength of polymer-metal hybrid. The oxide film on the metal surface was removed by caustic soda and nitric acid solution. After that, the metal surface was treated by fiber laser, and the hot pressing connection between polymer and metal was completed by plate vulcanizing machine. And then, the tensile strength was obtained by using universal testing machine. The effect of different laser power, different scanning line width and different scanning speed on the bonding strength of polymer-metal hybrid was investigated. The correlation between the characteristics of metal surface and the bonding strength of polymer-metal hybrid was analyzed based on the micro structure morphology and scanning electron microscope (SEM). The results show that the bonding strength of polymer-metal hybrid increases first and then decreases with the increase of laser power. With the increase of scanning line width, the strength of polymer-metal hybrid increases. When the scanning speed is 500 mm/s, the strength of polymer-metal hybrid is the lowest. Based on the experiment, a simplified model is established and analyzed. Through using ABAQUS to conduct the numerical simulations, the results are consistent with the theoretical analysis and experimental data.